Depositional setting of the southern arms of Lago Argentino (southern Patagonia). Issue 2 (9th December 2020) - Lozano, Jorge; Donda, Federica; Bran, Donald; Lodolo, Emanuele; Baradello, Luca; Romeo, Roberto; Vilas, Juan Francisco; Grossi, Maurizio; Tassone, Alejandro
ABSTRACT: Lago Argentino hosts a series of calving glaciers originating from the Southern Patagonian Icefield, the largest temperate ice cap of the southern hemisphere. Brazo Rico and Brazo Sur are two basins located in the southern part of Lago Argentino, where a series of high-resolution seismic profiles have allowed reconstruction of its depositional setting and sedimentary architecture, and to produce the following maps: top of the acoustic basement, top of the glacial sequence, and thickness of the glacio-lacustrine deposits. Data reveal the role of basement highs in the complex dynamic behavior of the two main glaciers, Perito Moreno and Frías glaciers, which fluctuated along Brazo Rico and Brazo Sur since the end of the Last Glacial Maximum. Their advances and retreats are testified by the presence of several moraine fronts buried beneath a generally undisturbed, glacio-lacustrine and lacustrine sequence, which records the depositional history of the southern arms of Lago Argentino.